Contribution of Principal Leadership and School Culture Through Teacher Performance to School Quality - Hilga, Dwi Setyowati; Udik Budi Wibowo (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to examine the direct and indirect impacts of school culture and principal leadership on school quality as measured by teacher performance in Wonosobo Regency, Central Java Province. The main problem in this study is how the relationship between school culture, principal leadership, and teacher performance in shaping school character. This study uses a quantitative approach with a path analysis method to evaluate the relationship between these variables. The research subjects consisted of 91 participants who were prospective teachers from the sixth group in Wonosobo Regency. Data analysis techniques included classical assumption tests, path analysis with trimming techniques, and the Sobel test to test the mediation effect. The results indicate that principal leadership does not directly affect teacher performance, but is directly influenced by school culture. Teacher effectiveness is the result of the combined influence of school culture and principal leadership. In addition, school culture, principal leadership, and teacher performance contribute to the formation of school character. Teacher performance acts as a direct mediator between principal leadership and school character, as well as an additional mediator between school culture and school character. The conclusion of this study emphasizes the importance of strengthening school culture and the role of teacher performance in improving the quality of school character.